Adsorption of copper in oxisol and alfisol - Lopes, Claudia; Campos, Mari Lucia; Souza, Maurício de; Silveira, Cristian Berto da; Pelozato, Michelle (Revista de Ciências Agroveterinárias, 2014)
The accumulation of copper (Cu) in soil can provide input in excess of these elements in the food chain through the contamination of soil and water. The study of the chemical behavior of Cu is needed for the knowledge of mobility of these elements in the soil profile. The aim of this study was to know the background Cu concentration, to evaluate the effect of pH, ionic strength (FI) and to quantify the maximum adsorption capacity (CMA) of Cu in Oxisol and Alfisol. The adsorption rate was evaluated at pH 4.5, 5.5 and 6.5 and the FI 15 and 150 mmol L-1 of Ca(NO3)2. To quantify the CMA were used rates of Cu concentrations of 0, 0.075, 0.15, 0.30, 0.60, 1.5 mmol L-1, final soil: solution l: 100. Raising the pH value increased the adsorption of Cu and increasing the ionic strength of the solution didn’t reduce the adsorption of Cu. The CMA calculated for Cu in Alfisol was 3354 mg kg-1. It was not possible to calculate the CMA in Oxisol.